Molecular proxies as indicators of freshwater incursion-driven salinity stratification - Tulipani, Svenja; Grice, Kliti; Greenwood, Paul; Schwark, Lorenz; Böttcher, M.; Summons, R.; Foster, C. (Elsevier Science BV, 2015)
Salinity-related stratification in marine environments is one of the main drivers for the development of persistent anoxia and euxinia. It therefore plays a vital role in the sedimentary preservation of organic matter and has also been associated with Oceanic Anoxic Events during several mass extinctions in Earth's history. Here we present a novel molecular proxy using relative abundances of methyltrimethyltridecylchromans (MTTCs) as indicators of riverine freshwater incursions into Middle to Late Devonian paleoreefs exposed to conditions of prevailing anoxia, photic zone euxinia and water column stratification. This paper aims at re-instigating a discussion about the origin of these compounds to potentially broaden their utilization as paleoproxies, adding freshwater stratification to the general salinity reconstructions. The co-variation of MTTC abundance profiles and δ13C values with other biomarker parameters in the sediments studied here indicate a link of MTTCs to terrigenous input, pointing towards a previously suggested early diagenetic formation of these compounds from phytol with higher plant-derived alkylphenols.